Group cognitive remediation therapy for adult anorexia nervosa inpatients: first experiences - Žuchová, Svetlana; Erler, Theodore; Papežová, Hana (Eating and weight disorders, 2013)
AIM: In this study, we aim to explore the feasibility and acceptability of group cognitive remediation therapy (CRT) for anorexia nervosa (AN) inpatients, and to suggest modifications for future use. METHODS: We performed ten 45-min CRT sessions, once a week, in two consecutive groups of adult AN inpatients. The groups consisted of 14 and 20 participants, respectively. At the end of each session, participants filled in a questionnaire asking them to evaluate whether and how they benefited from the exercise RESULTS: Group-based CRT could be well incorporated into the therapeutic program of the Eating Disorders Unit, and was well received by the participants. Based on patients' feedback and our observations, we discuss several options for future modifications.
Keywords: kognitivně behaviorální terapie; spokojenost pacientů; dospělí; průzkumy a dotazníky; Female; Adult; Patient Satisfaction; výsledek terapie; ženské pohlaví; mladý dospělý; Surveys and Questionnaires; Adolescent; lidé; Inpatients; skupinová psychoterapie; Treatment Outcome; mentální anorexie; Male; Young Adult; Psychotherapy, Group; lidé středního věku; Anorexia Nervosa; mužské pohlaví; Middle Aged; mladiství; hospitalizovaní pacienti; Cognitive Behavioral Therapy; Humans